Design and Optimization of Collimator for Preclinical Single-photon Emission Computed Tomography Scanner: A Monte Carlo Study - Mohammad Mirdoraghi; Behnoosh Teimourian Fard; Olga Kochebina; Hojjat Mahani; Mohammad Reza Ay (Journal of Medical Physics)
Introduction: Small animal imaging has an extensive variety of applications, including the design and optimization of novel imaging devices. Monte Carlo (MC) simulations are enhanced due to their high accuracy. The purpose of this investigation was to implement and validate a MC model for a preclinical single-photon emission computed tomography (SPECT) known as high-resolution SPECT II (HiReSPECT II) machine developed in our laboratory and also optimize different collimator materials and geometries for improving the sensitivity and spatial resolution. Materials and Methods: The validation of a small animal SPECT scanner equipped with lead hexagonal parallel-hole collimator, CsI (Na) pixelated crystal, and SiPM photodiodes was performed by comparing experimental results with Geant4 application for tomography emission (GATE) simulation data. In the next step, the optimization appraisals for both spatial resolution and sensitivity on the collimator material (W and Pb) and hole diameter were carried out using GATE. The experimental and simulated sensitivities were obtained using a cylindrical phantom at source to the collimator distance (SCD) of 3 cm. Moreover, a line source was applied to assess the spatial resolution in the simulated and experimental environments at different SCDs. Besides, a tungsten collimator with a hole diameter of 0.99 mm is suggested. 99mTc was used as the radionuclide in all experiments. Results: The discrepancy between experimental and simulated sensitivities was <3%. In addition, the differences between simulated and experimental spatial resolutions were about 5%. Furthermore, the optimized hole diameter for tungsten is 0.99 mm according to the curve representing the tradeoff between spatial resolution and sensitivity. Conclusion: Lead exhibits a little higher sensitivity compared to tungsten because it has superior penetration and scattering abilities, leading to an increased full width at the tenth maximum that can diminish the spatial resolution. In addition, enlarging the diameter of the holes increases the number of photons that penetrate and scatter, thereby reducing the spatial resolution. The proposed collimator is able to provide adequate sensitivity considering the spatial resolution achieved at the SCD of 3 cm.